PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR PESERTA DIDIK (Studi Pada Mata Pelajaran Fisika Kelas X TR SMK Negeri Pagar Alam) - Mimi Hartini (DIADIK, 2021)
This study aims  to describe the application of the Guided Inquiry learning model to increase the participation and learning achievement of students, as well as describing the effectiveness of the Guided Inquiry learning model application that can improve student learning achievement. This research is a Classroom Action Research (CAR) which is carried out in three cycles then followed by a quasi experiment.  Each cycle consists of four stages, namely planning the action, implementing the action, observing, and reflecting.  The subjects of this study were students of class X TR at SMK Negeri Pagar Alam in the academic year 2020/2021. The technique of collecting data through observation and tests.  Technique of data analysis using the mean formula and t test.  From the research results it can be concluded that the application of the Guided Inquiry learning model can increase the participation and learning achievement of students, as well as effectively improve the learning achievement of class X TR students at SMK Negeri 1 Pagar Alam.